Exploring the microbiome of black soil from central India and the impacts of agricultural practices on soil microbial communities - Sudhir Kumar; Rituja Saxena; Rajesh Saxena; Vineet K. Sharma (Annals of Microbiology)
Abstract Background Healthy microbial communities in the soil are indispensable for agricultural productivity. The diversity in physiochemical properties, their geological origins, and local climatic conditions lead to the evolution of diverse soil types with distinct bacterial communities. Despite global distribution, the microbial composition of black soil remains largely unexplored. Here, we investigated the composition, diversity, and functional potential of bacterial communities in black soils from central India. We also examined how common agricultural disturbances e.g. the use of chemical and organic fertilizers, crop growth, and crop species impacted soil communities in a three-year longitudinal field experiment involving three crops. Results The black soil core microbiome was dominated by phyla Actinobacteria and Proteobacteria members. Analysis of bacterial composition in vermicompost revealed the presence of plant growth-promoting taxa. Among the assessed cropping practices, crop growth significantly affected microbiome composition in soil. We also observed the impact of crops in selectively enhancing the soil microbiome, highlighting the role of plant species in shaping community structure. Notably, soil cultivated with chickpea exhibited an enrichment of multiple Rhizobiales members, including Devosia, Pseudolabrys, and Tepidamorphus. During this experiment, fertilizer treatment did not influence the microbiome significantly. Overall, the data showed the vulnerability and resilience of soil bacterial communities to agricultural disturbances. Conclusion The microbial composition of black soil in central India was revealed, and the effects of agricultural management on black soil microbial composition were evaluated. The prominent impact of individual plants showed the role of plant-root microbiome interactions in shaping the composition of soil communities. Fertilizer application did not show significant effects during the field experiment, reflecting the resilience of soil communities to short-term disturbances. We also shed light on the functional metagenomic potential of black soil communities and the effect of common agricultural disturbances in a prominent soil type.